Cross-linguistic analysis of discourse variation across registers - Kunz, Kerstin; Lapshinova-Koltunski, Ekaterina (Nordic journal of English studies, 2015)
The present study deals with variation in discourse relations in different registers of English and German. Our previous analyses have been concerned with the systemic contrasts between English and German, cf. Kunz & Steiner (2013 a/b), Kunz & Lapshinova (to appear) and have addressed some cross-linguistic differences with regard to textual realizations of selected subtypes of cohesion. In our current work, our focus is on the empirical analysis of cross-linguistic variation between registers. In order to obtain a more comprehensive picture, we investigate three main types of cohesion in combination: co-reference, substitution and conjunction and their subtypes, cf. Halliday & Hasan (1976). We extract instantiations of cohesive devices from an English-German corpus of spoken and written registers. The data is analyzed with statistical procedures which show that subcorpora can be grouped along particular combinations of cohesive devices.